Training needs for municipal employees: a case study of Makana Municipality - Hamaamba, Tyson (Rhodes University, Faculty of Education, Department of Education, 2005)
This study investigated the education and training needs for municipal employees in order to inform an education and training strategy that would address environmental management challenges in Makana local municipality in Grahamstown, Eastern Cape province. The research was conducted as a qualitative case study that made use of questionnaires, document analysis, focus group discussions and interviews as instruments for data generation. Samples of respondents were selected from Makana Municipality employees in top and middle management positions, professionals/technicians and workers, including elected councillors. The study was contextualised through establishing environmental management issues in Makana municipality; establishing organisational needs; development of a learner profile; and through a review of policies and recent trends in adult education. The study established that the Makana Municipality employees are most concerned with the following issues: sanitation; solid waste management; livestock management and fire management. These issues require primary environmental competences among all council employees (top and middle management, professionals and technicians, workers and councillors who work on part-time basis). The educational implications needed to respond to these issues also require an understanding of legislation. The study also established that technical education and training which includes planning, project management, and financial and budgeting competences are necessary amongst the management and professionals. These competences may enable them to develop capacity in environmental management. This study further established the need for social education which includes competences such as communication and social justice. These competences should be developed amongst members of the same group as they need to involve the community in management of the environment. This should enable the municipality to create job opportunities and help change negative attitudes.
Keywords: Municipal officials and employees -- Training of -- South Africa -- Grahamstown; Environmental education -- South Africa -- Grahamstown; Local officials and employees -- Training of -- South Africa -- Grahamstown; Municipal water supply -- South Africa -- Grahamstown; Sanitation -- South Africa -- Grahamstown; Environmental health -- South Africa -- Grahamstown; Environmental management -- South Africa -- Grahamstown; Livestock -- Management -- South Africa -- Grahamstown; Refuse and refuse disposal -- South Africa -- Grahamstown; Fire departments -- South Africa -- Grahamstown